INNOVATIVE ECOSYSTEMS AND COOPERATION OF UKRAINIAN UNIVERSITIES WITH BUSINESS AND PUBLIC INSTITUTIONS - Konovalenko, Tetiana (Studies in Comparative Education, 2025)
The article discusses the state of innovative ecosystems in Ukraine and the experience of their functioning in the European Union. The author outlines the notion of innovative ecosystems and describes some cases of Ukrainian and European cases of organizing and functioning of innovative ecosystems on the basis of universities in cooperation with business, enterprises and public institutions. The strengths and weaknesses of Ukrainian ecosystems from the results of other Ukrainian and foreign research, analytical reports represented by Ukrainian ministries and international organizations, Ukrainian and European databases, the official sites of Ukrainian higher education institutions, the project reports of their participants are analysed, the prospects for new opportunities are described. The impact of international projects and programmes on the development of innovative ecosystems is studied. The outline of such programmes as Horizon Europe, Erasmus+, Digital Europe Programme, Junior Achievement Ukraine is presented as the most valuable for Ukraine as they support innovative projects and ecosystems within their scope regarding separate economy sectors and directions. Besides considering the separate projects or experiences focusing on creation, functioning or improvement of innovative ecosystems in Ukraine, Italy, Czech Republic and Latvia, the article presents the experience of addressing the issues of innovative ecosystems within the third mission of a university and the interim result of Erasmus+ project “Universities - communities: strengthening cooperation”.